2013
DOI: 10.1186/1556-276x-8-251
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanoparticles of platinum on chicken embryo development and brain morphology

Abstract: Platinum nanoparticles (NP-Pt) are noble metal nanoparticles with unique physiochemical properties that have recently elicited much interest in medical research. However, we still know little about their toxicity and influence on general health. We investigated effects of NP-Pt on the growth and development of the chicken embryo model with emphasis on brain tissue micro- and ultrastructure. The embryos were administered solutions of NP-Pt injected in ovo at concentrations from 1 to 20 μg/ml. The results demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 36 publications
1
52
0
Order By: Relevance
“…On the other hand, some researchers showed that the numbers of nonviable fetuses was significantly increased in dams treated to a single oral dose of 10 mg/kg/B.wt AgNPs not higher doses, this due to facilitation of aggregation AgNPs at higher concentration in gut and preventing internalization via the gastrointestinal tract and so reducing fetotoxicity at higher doses, this result agree with [22]. Other study showed many pathological changes in the brain structure in chicken embryos treated with platinum nanoparticles NP-Pt, showing a moderate degradation of the cerebellar molecular layer, loss in neural cells in the cerebellum cortex, and astrocytosis [23]. In this study, we observed that AgNPs when administration to pregnant rats at concentration (2, 20mg/kg/B.wt) not have seen mortality in dams, while, other study found that administration of 20 mg silver ion led to the death of more than half pregnant rats in group after 1 ml injection, due to that silver nanoparticle is less toxicity than silver ions [24].…”
Section: Discussionsupporting
confidence: 72%
“…On the other hand, some researchers showed that the numbers of nonviable fetuses was significantly increased in dams treated to a single oral dose of 10 mg/kg/B.wt AgNPs not higher doses, this due to facilitation of aggregation AgNPs at higher concentration in gut and preventing internalization via the gastrointestinal tract and so reducing fetotoxicity at higher doses, this result agree with [22]. Other study showed many pathological changes in the brain structure in chicken embryos treated with platinum nanoparticles NP-Pt, showing a moderate degradation of the cerebellar molecular layer, loss in neural cells in the cerebellum cortex, and astrocytosis [23]. In this study, we observed that AgNPs when administration to pregnant rats at concentration (2, 20mg/kg/B.wt) not have seen mortality in dams, while, other study found that administration of 20 mg silver ion led to the death of more than half pregnant rats in group after 1 ml injection, due to that silver nanoparticle is less toxicity than silver ions [24].…”
Section: Discussionsupporting
confidence: 72%
“…Similarly, platinum NP also did not affect the growth and development of chicken embryos [Prasek et al, 2013]. Nevertheless, NP induced apoptosis ( table 3 ) and decreased the number of proliferating cells in the brain tissue [Prasek et al, 2013].…”
Section: Embryonic Toxicity Of Np In Animal Models: Avian Embryosmentioning
confidence: 89%
“…Nevertheless, NP induced apoptosis ( table 3 ) and decreased the number of proliferating cells in the brain tissue [Prasek et al, 2013]. On the other hand, concentrations of platinum NP were lower in chicken embryos in comparison to zebrafish [Asharani et al, 2011].…”
Section: Embryonic Toxicity Of Np In Animal Models: Avian Embryosmentioning
confidence: 98%
“…NP made of noble metals have been also used in brain delivery for theranostic purposes [317] , [325][326][327]. Neurotoxicity of silver in the brain has already been reported after systemic, intracerebral and intranasal administration [321,325,328,329].…”
Section: In Vivo Toxicity Of Nanomaterialsmentioning
confidence: 99%